The influence of principal leadership, competence, and organizational commitment on teacher performance at SMKN 10 Pandeglang - Asep Suhandi; Anisa Faijah; Ulfi Ulfi; Wahid Sumarjo; Tajudin Tajudin (Enrichment : Journal of Management, 2026)
This study aims to evaluate the influence of principal leadership, teacher competence, and organizational commitment on teacher performance at SMKN 10 Pandeglang, both individually and collectively. Using a quantitative research design, the study seeks to provide empirical evidence on how these factors contribute to improving teachers’ professional performance. Data were collected through a standardized questionnaire distributed to all 71 teachers at SMKN 10 Pandeglang, applying a census sampling technique to ensure full population participation. The hypothesis testing results reveal statistically significant relationships between the examined variables and teacher performance. Specifically, teacher competence was found to have a positive and significant effect on performance, as indicated by a calculated t-value of 2.241 exceeding the critical value of 1.966 and a significance level of 0.03, below the 0.05 threshold. Additional hypothesis testing further supports the substantial role of teacher competence in enhancing performance. Moreover, the combined influence of principal leadership, teacher competence, and organizational commitment was shown to significantly affect teacher performance, demonstrated by a t-value of 3.828 and a significance level of 0.00. These findings are reinforced by the F-test results, where the calculated F-value of 8.048 exceeds the table value of 2.628, confirming the strong collective impact of the three variables